STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MEWUJUDKAN BUDAYA SEKOLAH RAMAH ANAK BERBASIS PEMBELAJARAN MENDALAM - Annisa, Sofia; Priono, Rizka Fadhilah; Nainggolan , Adellina Ahmad Zain; Azhari , Saadah; Winara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the leadership strategy of the principal of SDN 064990 Medan Johor in realizing a child-friendly school culture based on immersive learning. This study uses qualitative and descriptive methodologies. The principal, instructors, students, and parents served as research informants, and information was collected through observation, interviews, and documentation. The research findings provide indications that the principal's leadership strategy is implemented through three main strategies: transforming school policies through revising the vision and mission and managing resources that favor students; strengthening teacher competencies and implementing immersive learning; and building a child-friendly school culture through strengthening social interaction, collaboration, and continuous evaluation. Various programs such as Mission Morning, the use of mood emoji symbols, teacher learning communities, digital media development seminars, and parent involvement have been proven to support the creation of a safe, comfortable, inclusive, and student-centered learning environment. The results of the study provide indications that the success of a child-friendly school culture based on immersive learning is greatly influenced by the principal's skills in integrating policies, human resource development, and school culture in a sustainable manner.